2017
DOI: 10.1016/j.bpj.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Large Hypericin Aggregates in Giant Unilamellar Vesicles—Experiments and Modeling

Abstract: The incorporation of hypericin (Hyp) from aqueous solutions into giant unilamellar vesicle (GUV) membranes has been studied experimentally and by means of kinetic Monte Carlo modeling. The time evolution of Hyp fluorescence originating from Hyp monomers dissolved in the GUV membrane has been recorded by confocal microscopy and while trapping individual GUVs in optical tweezers. It was shown that after reaching a maximum, the fluorescence intensity gradually decreased toward longer times. Formation of oversized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…These findings indicate that the encapsulation of hypericin as inclusion complex instead of free hypericin resulted in higher entrapment efficiencies for DSPC carriers. It has been shown that hypericin tends to form aggregates in giant unilamellar vesicles (GUV) (Joniova et al., 2017). Conclusively, it can be assumed that the formation of hypericin clusters which are removed by SEC lead to a reduced amount of hypericin bound to the DSPC membrane.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that the encapsulation of hypericin as inclusion complex instead of free hypericin resulted in higher entrapment efficiencies for DSPC carriers. It has been shown that hypericin tends to form aggregates in giant unilamellar vesicles (GUV) (Joniova et al., 2017). Conclusively, it can be assumed that the formation of hypericin clusters which are removed by SEC lead to a reduced amount of hypericin bound to the DSPC membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Similar absorption spectra, ascribable to the monomeric form of HYP, have been previously reported for the incorporation of this molecule in membranes, nanoparticles or proteins. 59 As for fluorescence, HYP@1 in PBS shows a fluorescence emission spectrum with band maxima at 597 and 647 nm while HYP in PBS shows no fluorescence under the same conditions. These results also point to the presence of free HYP in the nanogels and aggregated, non-emissive, HYP in the aqueous medium.…”
Section: Hypericin Loaded Nanogelsmentioning
confidence: 95%
“…22,23 Selfaggregation of hypericin in circulation creates large clusters that can impact biological function, as well as hypericin distribution and clearance. 24,25 Large hypericin aggregates have been observed in mononuclear phagocyte system (MPS) organs leading to slow clearance. Moreover, non-aggregated hypericin formulations have been shown to have signicantly improved necrosis affinity in vivo compared with hypericin aggregates.…”
Section: Synthesis Of Au-hyp-npmentioning
confidence: 99%